Milling properties of desi and kabuli chickpea (Cicer arietinum) varieties released in India - SRIVASTAVA, A K; DIXIT, G P; KUMAR, NARENDRA (The Indian Journal of Agricultural Sciences, 2017)
Dal milling is among top three grain processing industries in India. Milling performance of pulses varies with grain property and milling methodologies with a key role played by the genotype. More than 190 varieties of chickpea belonging to both desi and kabuli types have been released in India mainly on the basis of yield and disease reaction, ignoring the miller and traders preferred processing traits. There is dearth of information about milling performance of chickpea varieties cultivated in India. The present study provides milling potential of 46 popular chickpea varietieswhich are currently in seed chain in the country. Although kabuli type chickpea varieties are mostly consumed as whole seed, yet they were included in the study for comparing their milling potential with desi types. The kabuli varieties exhibited better dal recovery (83.1-87.8%) than desi (61.3-82.6%) along with lesser soaking period (90-240 min) and chaff content (8-13.6%) due to their thinner seed coat. The kabuli types exhibited poor grain yield (944-1764 kg/ha) as compared to desi types (811-2558 kg/ha). The difference in yield among desi and kabuli types was compensated in dal yield to some extent due to better dal recovery (%) among kabuli types. Among desi varieties, soaking period and chaff content was positively correlated indicating that more the chaff content more will be the soaking duration and vice versa. The dal recovery was positively correlated with 100-seed weight and negatively correlated with chaff content. Dal recovery among desi varieties can be improved by reducing seed coat thickness. Desi varieties GNG-2144, RSG-963, RSG-974 and kabuli varieties IPCK 2002-29, CSJK-6, JGK-3 exhibited better milling propertiesand can be used as a donor for improved milling properties.